Recycling of Date By-Product for Mass Rearing of Peach Fruit Fly, Bactrocera zonata (Saunders) (Diptera: Tephritidae) - Amira Ahmed Kamel Hassan Negm; Akram Shawky Abd El-Maaboud; Abdallah Ali Elzouk; José Eduardo Serrão; Heba Abdel Aziz Seleem Elelimy (Brazilian Archives of Biology and Technology, 2023)
Abstract The world is currently facing a severe economic crisis and the rational consumption and reuse of products, including waste are necessary. Agriculture wastes have importance containing beneficial and economic value matters, which unutilized may lead to environmental pollution. Date seed is one of these viable wastes with high nutritional value. Mass rearing of peach fruit flies is important to produce parasitoids for use in biological control programs or sterile insect techniques. In this study powder of date seeds were evaluated as an alternative diet for mass rearing of peach fruit fly Bactrocera zonata. The nutrient composition of the tested diet that contained date seed powder was rich in crude proteins (13.1%), crude carbohydrates (40.41), crude fats (4.6), crude fibers (8.4), and ashes (0.29). The results indicated that the date seed powder produced insects with quality parameters equivalent to FAO, IAEA/USDA standards, without differences with those reared on yeast. The histology of the reproductive system of B. zonata reveals that the female ovariole is of meristic-polytrophic type with successive stages of egg chambers. The male testis has a single long follicle with successive stages of spermatogenesis. Thus, date seed powder is a potential alternative diet for use in the mass rearing of the peach fruit fly.